(untitled) (Web of Teachers: Inderscience Research, 2025)
Our article is devoted to the analysis of long-term economic forecasts for the global economy in 2050. In the article, we consider the key factors that will affect the development of the global economy, such as demographic change, technological innovation, sustainable development and climate change. It is expected that in 2050 the world economy will be characterized by a high degree of digitalization, sustainable development and adaptation to climate change, which will require fundamental changes in the economic policy of countries and international relations.